2023
DOI: 10.3390/foods12122328
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Odor-Active Compounds from Gryllus bimaculatus Using Gas Chromatography-Mass Spectrometry-Olfactometry

Abstract: Edible insects have recently attracted attention as an alternative sustainable protein food source. However, consumer aversion remains the major obstacle to successful implementation in the food industry due to their shape and unpleasant odor. Here, we evaluated and compared odor-active compounds from untreated Gryllus bimaculatus (UGB), hot-air dried GB at 70 °C for 10 h (AGB), freeze-dried GB (FGB), steam-heated GB at 121 °C and 14.5 psi for 15 min (SGB), and defatted GB by hexane (DFGB). Each sample was ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Cricket volatile compounds are among the factors affecting flavor; for instance, they are responsible for cricket-related odor [ 24 ]. In previous research, approximately 40–60 volatile compounds have been identified in edible cricket powder, 14 of which have also been determined as being related to cricket-related odor [ 24 , 25 , 26 ]. In this study, we identified approximately 50 volatile compounds in both cricket powders ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cricket volatile compounds are among the factors affecting flavor; for instance, they are responsible for cricket-related odor [ 24 ]. In previous research, approximately 40–60 volatile compounds have been identified in edible cricket powder, 14 of which have also been determined as being related to cricket-related odor [ 24 , 25 , 26 ]. In this study, we identified approximately 50 volatile compounds in both cricket powders ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%